Itch: from the skin to the brain – peripheral and central neural sensitization in chronic itch - Mahmoud, Omar; Oladipo, Olusola; Mahmoud, Rami H.; Yosipovitch, Gil (Frontiers in Molecular Neuroscience, 2023)
Similar to chronic pain, chronic itch is frequently linked to neural sensitization, a phenomenon wherein the nervous system becomes hypersensitive to stimuli. This process of neural sensitization of chronic itch is orchestrated by various signaling pathways and mediators in both the peripheral and central nervous systems. At the level of the peripheral nervous system, inflammation and neuroimmune interactions induce plastic changes to peripheral nerve fibers, thereby amplifying the transmission of itch signaling. Neural sensitization in the central nervous system occurs at both the spinal cord and brain levels. At the level of the spinal cord, it involves hyperactivity of itch-activating spinal pathways, dysfunction of spinal inhibitory circuits, and attenuation of descending supraspinal inhibitory pathways. In the brain, neural sensitization manifests as structural and functional changes to itch-associated brain areas and networks. Currently, we have a diverse array of neuroimmune-modulating therapies targeting itch neural sensitization mechanisms to help with providing relief to patients with chronic itch. Itch research is a dynamic and continually evolving field, and as we grow in our understanding of chronic itch mechanisms, so will our therapeutic toolbox. Further studies exploring the peripheral and central neural sensitization mechanisms in the context of chronic itch are needed.